Fiber Density Index Correlates with Reduced Fractional Anisotropy in White Matter of Patients with Glioblastoma - Roberts, Tim P.L.; Liu, Fang; Kassner, Andrea; Mori, Susumu; Guha, Abhijit (American Journal of Neuroradiology, 2005)
Summary: A quantitative description of white matter fiber attenuation, the fiber density index (FDi) is described. This measure is derived from quantitative analysis of diffusion tensor imaging and reveals an index of the number of fiber paths traversing a region of interest. In this report, FDi is computed in 10 patients with glioblastoma multiforme, in white matter that is peritumoral and contralateral. FDi is shown to correlate significantly with fractional anisotropy.